Liberal democracy, education and social justice in Africa (Journal for Studies in Humanities and Social Sciences, 2015)
It is a widely accepted view that military and other forms of authoritarian rule were employed in the governance of certain African countries during the early years of postcolonial period from the 1960s to 1980’s as indicated by Bangura (1992), Harber (1997) and Leon (2010). Besides, a few socialist-oriented, independent one-party states existed. The latter years (1990s into the 21st century), saw many independent African countries embracing ‘liberal democracy’ accompanied by market economic models. The introduction of liberal democracy on the African continent has not been without its controversies however, as some African and Carribean social scientists such as Ake (1993 & 1996), Mafeje (2002), Lumumba-Kasongo, (2005), Ngwane (2006) and Sankatsing (2004), have blamed this system for being responsible for much social wretchedness across Africa. The question is: (a) to what extent has liberal democracy delivered social equity on the continent; and (b) in which way do liberal democratic policies promote or impede the aims of education in a democratic society? Arguing from a critical theory perspective, this Article explores the way in which liberal democracy as a system of governance put limitations on education’s capacity to play the transformative role within society. It suggests that liberal democracy advocates equality of opportunities for all at the expense of social justice; and that this prevent education from playing its role as a tool for achieving greater equity within society through promoting human, social and economic development.